Pengaruh Retorika Dakwah terhadap Pemahaman Wawasan Kebangsaan di Kalangan Milenial Muslim - Simatupang, Muhammad Andry; Nasution, Hasyimsyah; Azhar, Anang Anas (Islam & Contemporary Issues, 2025)
This study examines the influence of da'wah rhetoric on the understanding of national insight among Muslim millennials in Indonesia. In the context of rising social polarization and digital disruption, da'wah serves not only as a means of conveying religious teachings but also as a strategic medium for instilling national values such as tolerance, unity, and national identity. Contemporary Islamic preaching delivered through digital media by figures like Ustadz Hanan Attaki and Habib Husein Ja’far demonstrates the integration of religious messages with inclusive national narratives. This research employs a qualitative approach using thematic analysis, based on in-depth interviews with young Muslim audiences who actively engage with digital da'wah content. The findings show that contextual and participatory rhetorical approaches can enhance understanding and acceptance of national insight among the millennial generation. Rhetoric that touches emotional aspects, aligns with social realities, and uses language relatable to youth proves more effective in conveying nationalistic values. These findings highlight the importance of collaboration among preachers, religious institutions, and state bodies in designing da'wah strategies that strengthen social cohesion and national resilience. In the digital era, da'wah must evolve into a transformative force that not only provides spiritual guidance but also fosters a comprehensive national consciousness.